(untitled) (Journal of EAHIL, 2017)
Dear Colleagues, I’d like to begin this letter with a thanks to Sally Wood-Lamont, who with this issue of Journal of EAHIL, announces her resignation as Chief Editor. Sally has been instrumental in shaping the Journal and its growth from a newsletter - she has had wonderful vision, creativity, energy and impressive powers of logistical coordination. Sally will be giving more time to work with the Paralympic teams - they are exceptionally lucky to have her leadership, and we wish Sally and the teams every success. On behalf of all EAHIL members, I thank you, Sally! We will miss you very much!